Experience of hormone replacement therapy among women of Sarawak, Malaysia - Syed Alwi, S.A.R; Siti Rubiah, Zainuddin; Lee, P.Y.; Mallika, Premsenthil; Md Haizal, M.N. (Thomson Reuters, 2010)
Objectives To determine the usage of hormone replacement therapy (HRT) and knowledge about HRT among women of Sarawak in Malaysia. Methods A prospective study using a face-to-face interview was conducted on 356 randomly selected Sarawakian women aged between 40 and 65 years. Results The mean age of respondents was 50.83+6.30 years and the mean age of menopause was 51.28+2.28 years. Twenty-three percent of women were premenopausal, 39.6% perimenopausal and 37.4% postmenopausal. Only 36% of the respondents were aware of the existence of HRT; this is especially among those who were younger women, better educated and working. The main sources of information on HRT were friends and relatives (92.2%), newspapers/magazines (89.1%) and television/radio (64.1%). HRT usage among respondents was low (8.1%), mainly for relief of menopausal symptoms such as night sweats (100%), mood swings (93.1%), irritability (93.1%), and hot flushes (86.2%); only 24.1% used it for the prevention of osteoporosis. All women on HRT had taken HRT for less than 3 years. The main reason given for not being on HRT was that it was not recommended by their doctors (56.6%); only 8.3% worried about the side-effects and 4.3% were on other forms of treatment. Conclusions The use of and knowledge about HRT among women of Sarawak were found to be low in our study. The main sources of information about HRT are from friends/relatives and the mass media. Health-care providers should play an important role in promoting, counseling and health education regarding HRT needs to rectify these problems.